2019
DOI: 10.1002/jac5.1118
|View full text |Cite
|
Sign up to set email alerts
|

Precision pharmacotherapy: Integrating pharmacogenomics into clinical pharmacy practice

Abstract: Precision pharmacotherapy encompasses the use of therapeutic drug monitoring, evaluation of liver and renal function, genomics, and environmental and lifestyle exposures; and analysis of other unique patient or disease characteristics to guide drug selection and dosing. This paper articulates real‐world clinical applications of precision pharmacotherapy, focusing exclusively on the emerging field of clinical pharmacogenomics. Precision pharmacotherapy is evolving rapidly, and clinical pharmacists now play an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 83 publications
1
43
0
Order By: Relevance
“…Pharmacists are very well positioned to make major contributions to the field of Precision Medicine given their knowledge and competencies 4,8,38‐49 . It is evidenced by their capability to adequately interpret actionable recommendations derived from PGx‐guided CDS tools and formulate independent clinical judgments, rendering the pharmacist‐provided CMM an ideal niche for PGx‐guided CDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists are very well positioned to make major contributions to the field of Precision Medicine given their knowledge and competencies 4,8,38‐49 . It is evidenced by their capability to adequately interpret actionable recommendations derived from PGx‐guided CDS tools and formulate independent clinical judgments, rendering the pharmacist‐provided CMM an ideal niche for PGx‐guided CDS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the American Society of Health‐System Pharmacists (ASHP) upheld the pharmacist's role in implementing PGx at clinical settings, which translates into improved outcomes, better drug selection, and increased patient safety 3 . Likewise, the American College of Clinical Pharmacy (ACCP) envisions the clinical pharmacogenomic implementation as an essential component of precision pharmacotherapy 4 . A feasible approach to integrate PGx into pharmacy practice is through Comprehensive Medication Management (CMM) services 5‐7 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of relative advantage, PGx initiatives should engage transplant stakeholders early in the process to define evaluation metrics and the value proposition to both providers and patients 44 . These metrics should then be systematically evaluated on a regular basis to understand the overall value of PGx testing in the SOT population 43,44 …”
Section: Discussionmentioning
confidence: 99%
“…The need for clinical pharmacist input in research and implementation efforts has also been recognized by professional societies and other health care providers, allowing pharmacists to further demonstrate their value in the health system. 61,62 Pre-and post-implementations efforts led by pharmacists in a pilot project at the University of Florida assessing genotypeguided antiplatelet therapy found that successful implementation required expertise in pharmacy informatics (for CDS development in the EHR), medication safety, medication-use policies and processes, and educational strategy development. 61 With a deep-rooted background in pharmacology and medication management, pharmacists can build upon their clinical services and help execute PGx efforts as the medical community works toward fully embracing its clinical implementation.…”
Section: Role Of Pharmacistsmentioning
confidence: 99%
“…Advanced PGx training opportunities are now available with the establishment of residencies and fellowships, certificate programs, and continuing education courses. The need for clinical pharmacist input in research and implementation efforts has also been recognized by professional societies and other health care providers, allowing pharmacists to further demonstrate their value in the health system 61,62 . Pre‐ and post‐implementations efforts led by pharmacists in a pilot project at the University of Florida assessing genotype‐guided antiplatelet therapy found that successful implementation required expertise in pharmacy informatics (for CDS development in the EHR), medication safety, medication‐use policies and processes, and educational strategy development 61 .…”
Section: Implementation Of Pharmacogenetics Into Clinical Practicementioning
confidence: 99%